2008
DOI: 10.1037/1528-3542.8.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Looking happy: The experimental manipulation of a positive visual attention bias.

Abstract: Individuals with a positive visual attention bias may use their gaze to regulate their emotions while under stress. The current study experimentally trained differential biases in participants' (N = 55) attention toward positive or neutral information. In each training trial, one positive and one neutral word were presented and then a visual target appeared consistently in the location of the positive or neutral words. Participants were instructed to make a simple perceptual discrimination response to the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
105
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(115 citation statements)
references
References 30 publications
5
105
3
2
Order By: Relevance
“…We believe that this state/trait dissociation allows for a better characterization of this episodic and chronic mental disorder. From a clinical perspective, it will be important to determine the following in future research (i) whether the training of the biases toward mood-relevant information may constitute a novel treatment for symptomatic BD episodes (see Wadlinger and Isaacowitz, 2008, for evidence in patients with MDD) and (ii) whether attentional biases toward threatening information constitute a marker of vulnerability for BD, and if so, what preventive strategies may be employed, particularly in high-risk relatives.…”
Section: Stimulus Category Number Of Fixations (% Of Total)mentioning
confidence: 99%
“…We believe that this state/trait dissociation allows for a better characterization of this episodic and chronic mental disorder. From a clinical perspective, it will be important to determine the following in future research (i) whether the training of the biases toward mood-relevant information may constitute a novel treatment for symptomatic BD episodes (see Wadlinger and Isaacowitz, 2008, for evidence in patients with MDD) and (ii) whether attentional biases toward threatening information constitute a marker of vulnerability for BD, and if so, what preventive strategies may be employed, particularly in high-risk relatives.…”
Section: Stimulus Category Number Of Fixations (% Of Total)mentioning
confidence: 99%
“…Fredrickson and colleagues (Fredrickson, et al, 2008) conducted a randomized longitudinal field experiment using an intervention called Loving-Kindness Meditation (LKM), a practice used to develop warm and caring feelings for oneself and others (Salzberg, 2004 Rowe, Hirsh, & Anderson, 2007), with eye-tracking (Wadlinger & Isaacowitz, 2008) and with brain-imaging studies (Schmitz, De Rosa, & Anderson, 2009;Soto et al, 2009). …”
Section: The Emotions Of Happiness and Well-beingmentioning
confidence: 99%
“…Two of these studies manipulated the attend group to threat or negative stimuli 39,40 and four, to positive stimuli. [41][42][43][44] The first two found that the treated groups increased AB for threat or negative stimuli when compared with the control groups. They also found that the effects correlated with higher anxiety scores 39 and were potentiated by explicit instructions before training.…”
Section: Depressionmentioning
confidence: 99%
“…Moreover, they had a negative correlation with anxiety, 42 stress reactivity, 43 fewer negative thought intrusions in a worry test 45 and generalization to other measures of stress. 44 Of the three studies that used only avoid groups, one did not conduct a post test because it did not find AB for threat at baseline, 46 whereas the other two found a reduction in the post-training AB, with effects generalized to other scales and self-reported symptoms of anxiety, worrying and depression. 45,47 However, the two studies 48,49 that used avoid, attend and control group found different results.…”
Section: Depressionmentioning
confidence: 99%
See 1 more Smart Citation